2015
DOI: 10.1371/journal.pone.0126142
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Adipogenesis and Key Adipogenic Gene Expression by 1, 25-Dihydroxyvitamin D in 3T3-L1 Cells

Abstract: The functions of 1, 25-dihydroxyvitamin D (1, 25-(OH)2D3) in regulating adipogenesis, adipocyte differentiation and key adipogenic gene expression were studied in 3T3-L1 preadipocytes. Five concentrations (0.01, 0.1, 1, 10, 100nM) of 1, 25-(OH)2D3 were studied and lipid accumulation measured by Oil Red O staining and expression of adipogenic genes quantified using quantitative real-time PCR. Adipogenic responses to 1, 25-(OH)2D3 were determined on 6, and 12 h, and days 1-10 after induction of adipogenesis by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 35 publications
5
37
0
Order By: Relevance
“…2b). These notions were confirmed by a recent study in the inhibitory effect of vitamin D on adipogenesis (Ji, Doumit, & Hill, 2015). …”
Section: Nutrients and Adipose Developmentsupporting
confidence: 65%
“…2b). These notions were confirmed by a recent study in the inhibitory effect of vitamin D on adipogenesis (Ji, Doumit, & Hill, 2015). …”
Section: Nutrients and Adipose Developmentsupporting
confidence: 65%
“…Our in silico analysis of TF-binding sites in proximity of macroH2A1.2 genome binding revealed that GATA-binding sites were overrepresented in the proximity of macroH2A1.2 binding in 3T3-L1 pre-adipocytes compared to differentiated cells, consistent with their role in adipocyte precursors and with their downregulation setting the stage for terminal differentiation. In mature adipocytes, RXRA::VDR and TP53-binding sites were enriched, which might reflect their anti-adipogenic transcriptional effects [33, 34]. The enrichment of consensus sequences for TF controlling homeobox genes, including the overrepresented PAX4, in macroH2A1.2 associates chromatin reads in the context of adipocyte differentiation deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is closely associated with diabetes mellitus and characterized by excessive growth of adipose tissue mass because of hyperplasia and hypertrophy of adipocytes. Inhibition of pre-adipocytes differentiation is one of the key therapeutic strategies to inhibit adipogenesis 3,4,5 . Our results showed that DMK significantly suppressed the adipogenic differentiation, lipid content and intracellular triglycerides in 3T3 L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Adipogenesis involves differentiation of pre-adipocytes into mature adipocytes and is regulated by two major adipogenic transcription factors namely, Peroxisome proliferator–activated receptor γ (PPARγ) and CCAAT/enhancer binding protein α (C/EBPα) and downstream induction of adipocyte-related genes including, adipocyte protein 2 (AP2), lipoprotein lipase (LPL), adiponectin etc. 3, 4, 5 .…”
Section: Introductionmentioning
confidence: 99%